Chorionic villous sampling-related complications: a cohort study - Kasemsri Srisupundit (2020)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Purpose: To compare the adverse pregnancy outcomes between the pregnant women undergoing chorionic villous sampling (CVS) and those without CVS. Materials and methods: A cohort study was conducted on low risk pregnancies attending Chiang Mai University Hospital between years 2003 and 2017 and identify the database of women undergoing CVS (study group) and control group. Each case in study group was matched for 10 cases of the control by maternal age and year of procedure. Results and conclusions: Of 1384 pregnancies undergoing CVS, 776 cases met criteria and were matched with 7760 controls. The gestational age at delivery and actual birth weight were significantly different between two groups (38.02 versus 38.96 weeks, p value <.001 and 3025 versus 3092 g, p value.001). Moreover, CVS group had significantly higher preterm birth (9.4 versus 7.3%, p value.037; RR 1.287, 95% CI 1.017–1.629). However, there was no significant difference in fetal loss rate before 24 weeks (1.16 versus 1.9%, p value.14), small for gestational age (SGA); SGA (4 versus 4%, p value.948) and low birth weight (LBW); LBW (8.9 versus 8.0%, p value.41). Pregnancies undergoing CVS tend to deliver earlier and has significantly higher preterm birth. However, the incidences of fetal loss, SGA and LBW are not significantly increased.